Preserving 40% forest cover is a valuable and well‐supported conservation guideline: reply to Banks‐Leite et al - Víctor Arroyo‐Rodríguez; Lenore Fahrig; James I. Watling; Justin Nowakowski; Marcelo Tabarelli; Lutz Tischendorf; Felipe P. L. Melo; Bráulio A. Santos; Maíra Benchimol; Jose Carlos Morante‐Filho; J. W. Ferry Slik; Ima C. G. Vieira; et al. (Ecology Letters, 2021)
Banks‐Leite et al . (2021) claim that our suggestion of preserving ≥ 40% forest cover lacks evidence and can be problematic. We find these claims unfounded, and discuss why conservation planning urgently requires valuable, well‐supported and feasible general guidelines like the 40% criterion. Using region‐specific thresholds worldwide is unfeasible and potentially harmful.